Protocolo de fluxo de cuidado domiciliar para a criança com necessidades especiais de saúde no Paraná - Rossetto, Vanessa (2017)
Introduction: Technological advances and the qualification of health professionals in the last decades have reflected in the epidemiological transition of childhood, with a reduction in infant mortality. In contrast, there was an increase in chronic conditions in childhood, evidencing Children with Special Health Needs - CRIANES. These require differentiated care, ranging from psychomotor and social rehabilitation, devices and technologies, drugs and differentiated care - to feed, sanitize and dress. Given this scenario, the need for changes in health care emerges and, in this context, Home Care (HC) can be considered as one of the responses of the system to meet the demands present in the chronic conditions. Objectives: To know and describe the care provided to the CRIANES in the services of Paraná State and to propose a protocol of home care flow, specific for these children. Methodology: Quantitative, case-study, descriptive and exploratory research. Data collection was performed through the application of an instrument developed for the research, to the professionals of all the Home Care Services - SAD of Paraná, by telephone and electronic mail, from October 2016 to January 2017. The data analysis was descriptive statistics. Secondly, a specific care flow protocol was developed for the CRIANES in the SAD, being guided by the methodology of reality analysis Strengths, Weaknesses, Opportunities and Threats (SWOT), from the diagnosis of the services. All the ethical precepts for human research were followed and the study was approved by an ethics committee in research. Results: The state of Paraná has accredited SAD in eight municipalities. Among the children attended by these, 25.7% of them have cerebral palsy and 60% are tracheostomized. Among the practices of the services it was observed that 25% of them use a therapeutic project, however 75% communicate inconstantly with primary care. It was highlighted as important points for the care of children in SAD2: scheduled hospital discharge, organized referral to the home care service, evaluation of effective eligibility, adequate preparation of the caregiver, organized sanitary transportation, systematic itinerary for admission, unique therapeutic project, shared care with primary care, systematized follow-up, organized telephone counseling, electronic and interconnected medical records, and specific flow in the emergency and emergency network. The weaknesses are mainly related to the low use of the therapeutic project and the counter reference to primary care. The method employed allowed a careful evaluation of each point involved and thus develop an action plan and flow chart that neutralizes weaknesses and threats and potentiates strengths and opportunities. Conclusions: Many successful practices are developed, but isolated in the municipalities. Thus, disseminating the positive experiences, this study fosters reflection and improvement of the work process and the development of the protocol offers subsidies to give robustness to the care of children with special health needs in home care.